Compartilhando um ambiente musical: processos educativos e relações afetivas entre pais e crianças de 8 a 24 meses - Raniro, Juliane (Universidade Federal de São Carlos, 2008)
The research work here presented has as a theretical base, authors that believe that the social practices and the people's educational processes are developed and favored in the context of their interactions with the family, friends and the community enviromment, Considering that music can create opportunities for the people's development, including mental, corporal and social aspects, this research has for objective to study the affectionate relationships that happen in music classes offered for a group of children of eight months to two years and the adults that accompany them in the musical activities offered in a music education programm. Starting from the idea that to share musical activities it is a social practice between babies and parents, a more attentive glance for the aspects involved in this practice also brings information on the educational processes that happen in elapsing of the interactions. The data were collected and analyzed through a methodology of qualitative research, involving participant observation. Photographic registrations of classroom situations, impressions and two specialist researchers' reflections in musical education, aided in the reception of images and prominence of significant situations for the construction of the data. The diary of the researcher's field and the conversations accomplished between she and the observers were fundamental for the understanding of the affectionate relationships revealed in elapsing of the research. Considering tha the organization and analysis of the data was possible to highlight that the solidarity, the knowledge and respect with the other, the friendship and the construction of affectionate bows, such as the touch, the affection, the change of glances, they were stimulated and noticed in different activities of musical practice. The interface between the data and the literature allowed to reveal how musical activities shared between parents and their babies can be important for the strengthening of affectionate bows and for the people's development.
Keywords: Educação musical; Educação musical para bebês; Processos educativos em ambientes musicais; Relações afetivas; Music education; Music education for babies; Educational processes in music classes; Musical practices; Affectionate relationships; CIENCIAS HUMANAS::EDUCACAO